2022
DOI: 10.1097/corr.0000000000002414
|View full text |Cite
|
Sign up to set email alerts
|

Race, Gender, and Primary Language Were Not Associated With Changes in Opioid Prescribing in Children: Results From a Single Institution, 2010 to 2020

Abstract: Background Patients should be prescribed medication based on their medical condition, without prejudice because of their race, gender, or primary language. However, previous research has shown that men are prescribed more medication than women, patients who are White are prescribed more medications than patients who are non-White, and English-speaking people are prescribed more medications than non-English-speaking patients. However, it is unclear whether these differences also occur in pediatric orthopaedic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The percentage of patients or observations with limited English proficiency ranged from 0.9% [46, 47] to 50% in a study that used matching to increase comparability between the language groups [30]. Of the studies that reported the frequencies of specific non-English languages in the sample, Spanish was the most common language in 10 studies [6, 17, 35, 39-41, 46, 47, 57, 63], Russian in one study [29], and Greek in one study [13] (Supplemental Digital Content 2; http://links.lww.com/CORR/B286). Two studies categorized the language exposure as English, Spanish, and other in their models [55, 63], and one study separately included six non-English-language categories as well as interpreter need in their primary model [29] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of patients or observations with limited English proficiency ranged from 0.9% [46, 47] to 50% in a study that used matching to increase comparability between the language groups [30]. Of the studies that reported the frequencies of specific non-English languages in the sample, Spanish was the most common language in 10 studies [6, 17, 35, 39-41, 46, 47, 57, 63], Russian in one study [29], and Greek in one study [13] (Supplemental Digital Content 2; http://links.lww.com/CORR/B286). Two studies categorized the language exposure as English, Spanish, and other in their models [55, 63], and one study separately included six non-English-language categories as well as interpreter need in their primary model [29] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…To address this aim, the findings from all studies were grouped by the three outcome categories for qualitative synthesis. Eight, 10, and 15 studies examined associations between limited English proficiency and clinical care processes [3,6,16,31,35,37,55,57], care processes related to patient engagement [7,11,23,29,39,46,47,49,61,63], and treatment outcomes [1,8,13,14,16,17,25,29,30,35,37,40,41,54,59], respectively. In each outcome category, we categorized the results into associations and no-difference findings and further stratified them as adjusted versus unadjusted estimates, conservatively categorizing estimates as unadjusted where unclear.…”
Section: Study Outcomesmentioning
confidence: 99%
“…This study [2] is important because it provides evidence that it is possible to give equal care to patients, at least regarding opioid prescriptions at discharge. We will need further studies on this topic as well as on other markers of care equality to determine whether this single-institution study in a diverse (46% non-White) urban center in the Northeastern United States is generalizable to other regions and healthcare settings and to better understand the existing discrepancies in access to and quality of care.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…First, it would be helpful to have more information in the form of studies like the current study, from other institutions, to evaluate the generalizability of Begley et al's [2] findings. Other institutions could perform similar types of inquiries either as internal audits for institutional quality improvement or published studies so results can be compared across institutions and so the landscape of care equity in pediatric orthopaedics can be better understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation